Testosterone therapy prevents gain in visceral adipose tissue and loss of skeletal muscle in nonobese aging men - Allan, C A; Strauss, B J G; Burger, H G; Forbes, E A; McLachlan, R I (The journal of clinical endocrinology and metabolism, 2008)
Trials of testosterone therapy in aging men have demonstrated increases in fat-free mass (FFM) and skeletal muscle and decreases in fat mass (FM) but have not reported the impact of baseline body composition. The objective of the study was to determine the effect, in nonobese aging men with symptoms of androgen deficiency and low-normal serum testosterone levels, of testosterone therapy on total and regional body composition and hormonal and metabolic indices. Sixty healthy but symptomatic, nonobese men aged 55 yr or older with total testosterone (TT) levels less than 15 nm were randomized to transdermal testosterone patches or placebo for 52 wk. Body composition, by dual-energy x-ray absorptiometry (FM, FFM, skeletal muscle) and magnetic resonance imaging (abdominal sc and visceral adipose tissue, thigh skeletal muscle, and intermuscular fat) and hormonal and metabolic parameters were measured at wk 0 and 52. Serum TT increased by 30% (P = 0.01), and LH decreased by 50% (P < 0.001). Relative to placebo, total body FFM (P = 0.03) and skeletal muscle (P = 0.008) were increased and thigh skeletal muscle loss was prevented (P = 0.045) with testosterone therapy and visceral fat accumulation decreased (P = 0.001) without change in total body or abdominal sc FM; change in visceral fat was correlated with change in TT levels (r2 = 0.36; P = 0.014). There was a trend to increasing total and low-density lipoprotein cholesterol with placebo. Testosterone therapy, relative to placebo, selectively lessened visceral fat accumulation without change in total body FM and increased total body FFM and total body and thigh skeletal muscle mass. Further studies are needed to determine the impact of these body compositional changes on markers of metabolic and cardiovascular risk.